Identification of microorganisms in vaginal swab and peritoneal fluid of women with endometriosis - Hadisaputra, Wachyu; Judio, Johny; Gunardi, Eka R (Indonesian Socety of Obstetrics and Gynecology, 2018)
Abstract Objective: to discover correlation between microorganisms found in vaginal swab culture and in peritoneal fluid culture from laparoscopy in reproductive age women diagnosed with endometriosis. Methods: This cross sectional study was conducted in Bunda Hospital and YPK Hospital, Central Jakarta. Thirty one subjects was includedby consecutive sampling. Data were analyzed using SPSS 20.0 for Windows. Bivariate analysis was used to identify the correlation between independent and dependent variable. Results: From 31 subjects with mean age 34.42+5.056 years old, 87.1% were infertile. Vaginal swab culture was found positive in 83.9% subjects while peritoneal fluid culture was found positive only in 9.6% subjects. There was moderate correlation between chronic pelvic pain and positive vaginal swab culture (r=0.601; p=0.001), but weak correlation between Ca125 and vaginal swab culture (r=0.440; p=0.010). Peritoneal fluid culture had significant inverse correlation with left tubal patency (r=-0.346; p=0.047). There was weak correlation between vaginal swab culture and peritoneum fluid culture with correlation coefficient of 0.13. Conclusion: Most of bacteria found in vaginal swab culture and peritoneal fluid culture were the ones found in gastrointestinal tract. However, vaginal swab and peritoneal fluid culture were not sufficient to prove the hypothesis that infection has a role in pathogenesis of endometriosis. Therefore, advance and more complete examination such as LPS and PCR might be needed to be done in the future research with cohort study, to overcome the limitation of this study. Keywords: endometriosis, ascending bacterial contamination, vaginal swab, peritoneal fluid, culture   Abstrak Tujuan : Membuktikan adanya korelasi antara mikroorganisme yang ditemukan pada hasil kultur bilasan vagina dengan mikroorganisme yang ditemukan pada cairan peritoneum hasil laparoskopi perempuan usia reproduksi yang terdiagnosis endometriosis Metode :Penelitian ini menggunakan desain penelitian analitik poltong lintang yang bertujuan untuk melihat adanya hubungan korelasi serta mengetahui tingkat korelasi antara mikroorganisme kultur bilasan vagina dengan mikroorganisme pada cairan peritoneum pasien endometriosis. Hasil: Hasil kultur bilasan vagina dari 31 subjek penelitian yang diteliti, mikroorganisme terbanyak adalah Enterococcus faecalis (32.3%), Eschericia coli (29.1%), dengan 16.1 % dengan hasil kultur negatif. Sedangkan dari hasil kultur bilasan peritoneum terdapat 3 subjek (9.6%) dengan hasil positif yaitu dengan jenis bakteri Eschericia coli, Enterococcus faecalis, dan Pseudomonas. Terdapat korelasi lemah antara hasil kultur bilasan vagina dengan kultur bilasan peritoneum (r 0.13). Terdapat korelasi sedang antara kultur positif bilasan vagina dengan nyeri pelvik kronis, korelasi lemah antara kultur positif bilasan vagina dengan nilai Ca 125, dan korelasi lemah antara kultur positif cairan peritoneum dengan tuba kiri yang non paten. Kesimpulan:          Sebagian besar bakteri dari bilasan vagina dan bilasan peritoneum pada pasien endometriosis memiliki hasil bakteri dari organ pencernaan. Terdapat korelasi lemah antara hasil kultur bilasan vagina dengan kultur bilasan peritoneum pada pasien endometriosis. Kata kunci: endometriosis, kontaminasi bakteri asenden, kultur, bilasan vagina, cairan peritoneum